(untitled) (Estudos em Design, 2020)
The focus of this paper is the issue of electronic game design as a teaching-learning methodology for university students in Brazil. Our aim is to discuss whether the Gamerama games educational experience can be characterized as a teaching methodology based on Design authors such as Imbesi (2011), Love (2002), Couto & Neves (1997) and Bomfim (1994); and electronic games authors, such as Salen & Zimmerman (2003), Schell (2010), Schuytema (2010), Fullerton (2008) and Brathwaite & Schreiber (2009). The research conducted seven field experiments, involving 175 students from different Brazilian schools and universities, and the data were evaluated using Content Analysis. We conclude that Design, as a field of technological and interdisciplinary knowledge, has principles, such as systemic thinking, that favor the development of game design methodologies, especially in the creation and development stage, which allow for the production of games with solid and socially responsible processes.